Prognostic significance of morphometric parameters of nucleoli and nuclei of invasive ductal breast carcinomas - Karpińska-Kaczmarczyk, Katarzyna; Kram, Andrzej; Kaczmarczyk, Mariusz; Domagała, Wenancjusz (Polish Journal of Pathology, 2009)
The aim of this study was to evaluate associations between seven morphometric parameters of the nucleoli and nuclei of methyl green and pyronin Y (MG-PY) stained tumour cells of invasive ductal breast carcinoma with relapse-free survival (RFS) and overall survival (OS) time. Histological sections from 150 invasive ductal breast cancers were stained with MG-PY and the following parameters were evaluated by computer image analysis: the nucleolar area, long to short nucleolar axis ratio, nucleolar shape parameter assessing the degree of nucleolar roundness, long to short nuclear axis ratio, number of nucleoli in the nucleus and the percentage of the nuclear cross-section surface area occupied by the nucleoli. A statistically significant association between a nucleolar shape polymorphism and the number of nucleoli in the nuclei of tumour cells and the RFS but not OS was found in the entire group of patients as well as patients with axillary lymph node metastases. A higher polymorphism of nucleolar shape and a higher number of nucleoli in the nuclei of breast cancer cells were associated with decreased relapse-free survival (p < 0.05). The remaining morphometric parameters showed no statistically significant association with RFS or OS. The results indicate that morphometry of nucleoli in MG-PY stained histological sections can be useful in the analysis of associations between nucleolar parameters and prognosis of patients with invasive breast cancer.